Sistema de controle automatizado de baixo custo para irrigação - Roston, Eduardo Santucci (Universidade Federal de São Carlos, 2021)
Automated irrigation systems, whether for commercial or residential purposes, are widely implemented with the aim of automating a recurrent task, in this case watering plants and crops, and for the smart use of water resources. This type of system is very prevalent in more developed countries, such as the USA, but the high price for its installation ends up becoming a financial barrier for many, especially in poorer countries like Brazil. The present work aims to develop one of the main components used in this type of system, the irrigation controller, responsible for coordinating the irrigation routines as well as switching the water flow to different irrigation areas, but with the difference of being an Open-Source and Open-Hardware low-cost controller. This controller has the objective of being a more cost-effective alternative, if compared to commercial competitors, aiming at the access of a larger public to this type of technology. The controller in question is an embedded system based on the Open-Source Arduino platform, using the ATmega328p microcontroller. It is composed of two printed circuit boards (PCB) operating together, the "Control Module", responsible for system control and automation of irrigation routines, and the "Driver Module", responsible for switching solenoid valves to allow water flow. At the end of the development of this work, it was verified that the main objective was reached, the developed controller presents a total cost significantly lower than that of commercial similar ones without sacrificing the main functions offered by higher price solutions.
Low cost automated irrigation control system
Keywords: Sistema embarcado; Sistema de irrigação; Irrigação automatizada; Eficiência hídrica; Embedded system; Irrigation system; Automated irrigation; Water efficiency; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS